Associations of Maternal and Child Fatty Acid Status With Child Growth and Development Outcomes in Ghana. (14th June 2022) - Fajardo, Jonnatan; Arnold, Charles; Adu-Afarwuah, Seth; Stewart, Christine; Oaks, Brietta; Dewey, Kathryn; Prado, Elizabeth
Abstract: Objectives: Maintaining adequate fatty acid intake during pregnancy and lactation is necessary to support fetal and infant growth. Low maternal intake may lead to decreased transfer of fatty acids to the fetus. Our objective was to examine associations of individual fatty acid status at three different time points with child growth and development outcomes at 18 months. Methods: A cohort of 1, 320 women were enrolled in the International Lipid-Based Nutrient Supplements Dyad Ghana trial (iLiNS-DYAD-G). Fatty acids were measured in maternal plasma at 36 weeks gestation (n = 130), maternal breast milk six months postpartum (n = 303), and child plasma at 18 months (n = 369) and quantified as weight percentage of total identified fatty acids of the sample (% weight). We examined correlations between time points (maternal, breastmilk, and child) for five indicators of fatty acid status: % weight of four individual fatty acids (alpha-linolenic acid, ALA; linolenic acid, LA; docosahexaenoic acid, DHA; arachidonic acid, AA) and the n6: n3 ratio (ratio of LA & AA to ALA, DHA & EPA). We then examined whether each fatty acid indicator was associated with child growth (head circumference for age, length for age, weight for length z-scores) or developmental outcomes (motor, language, and social-emotional scores) at 18 months. Adjusted regressions included child sex, food insecurity scores, socioeconomic status, intervention group, and years of maternal education. Results: Maternal plasma and breast milk were positively correlated for % weight AA, LA, and n6: n3 ratio. Maternal and child plasma were positively correlated for % weight DHA and n6: n3 ratio. Breast milk and child plasma fatty acids were positively correlated for % weight AA, ALA, DHA, and n6: n3 ratio. Associations of fatty acid status indicators with child growth and developmental outcomes were not significant after correcting for multiple comparisons. Conclusions: Although maternal fatty acid status was associated with breastmilk and child fatty acid status, maternal and child fatty acid status was not generally associated with child growth and development at 18 months of age in this sample of mother-child dyads in Ghana. Funding Sources: Bill & Melinda Gates Foundation; National Institute of Child Health and Human Development & Fogarty International Center R01HD099811.